Unveiling How Authentic Leadership Fosters Creativity : A TCCM-Based Systematic Literature Review and Future Research Agenda - Rastogi, Shweta; Prakash, Deepti; Sanjay Dhingra,; Bamel, Umesh (Prabandhan: Indian Journal of Management, 2026)
Purpose : Authentic leadership’s (AL) role in employee creativity is a pivotal area of study, given the need for organizations to foster innovation and adapt to changing market demands. Authentic leaders hold the potential to significantly influence employees’ creative capacities. Despite its importance, a significant gap exists in understanding how AL can considerably impact employees’ creativity. Our objective was to identify and analyse emerging patterns in the existing literature, theories, analytical methods, procedures, and attributes concerning this relationship. Methodology : A systematic review was conducted to extract data from 67 relevant articles using the Theory Context Characteristics Methodology (TCCM) approach. Findings : The study revealed that both individual traits and the broader organizational context play crucial roles in nurturing creativity. Key findings emphasized that AL fosters trust, supervisory support, and a psychologically safe environment, which are essential for unlocking employees’ creative potential. Practical Implications : Organizations could leverage these insights to develop leadership strategies that cultivate a work environment conducive to innovation and creative expression. Originality/Value : This research contributed to the literature by highlighting the nuanced ways in which AL could drive employee creativity, providing a robust foundation for future studies and practical applications.